Age Relationship with Ovarian Cyst Occurrence - Nurlaily Z, Sri; Hastuti R. Ali, Sri; Ibrahim, Fatmawati (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
It is very important for women of childbearing age to pay attention to reproductive health, because the fertility of a woman's reproductive organs is often associated with various diseases, including ovarian cysts. This study aims to determine the relationship between age and ovarian cysts. This type of research is an observational study with a cross sectional approach. The sample consisted of 115 respondents selected by total sampling. The research was conducted in July 2019 with a research duration of 7 days by collecting data directly from the register book from 2016 to 2018. The data was analyzed using the chi-square test to determine the relationship between age and the incidence of ovarian cysts. The results showed that the majority of respondents aged 20-50 years (at risk) who had ovarian cysts were 102 people (88.7%) and a small number of respondents aged <20 years and >50 years (not at risk) did not have ovarian cysts as many as 13 people (11.3%), with a statistically significant p-value = 0.002 <0.05. Conclusion: most of the respondents who were diagnosed with ovarian cysts were respondents aged 20-50 years (at risk). Keywords: Ovarian Cyst, Reproductive System, Age